Analysis Web Mining Technology to Predict the User Behavior in Multi-Media (International Journal of Engineering and Computer Science, 2018)
The fast growth of the Internet, we have entered a period of information explosion, there is a considerable measure of repetitive data in the Network. How to extract a useful part of this information from the massive information resources, dissecting the huge measure of data lastly get the potential information we need to extracted. Web mining innovation appeared and spared out the human from the data sea. This paper will break down the acknowledgment of Web content mining and Web structure mining, their essential algorithms standards, and their application areas.